EXPLORING THE NEXUS BETWEEN SERVICE QUALITY, PATIENT SATISFACTION, AND RECOMMENDATION INTENTIONS IN FAITH-BASED HOSPITAL SETTINGS - Ayu Christa Pratiwi Inaray; Fanny Soewignyo; Elvis R Sumanti; Deske W Mandagi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
More research is needed, particularly examining the connection between service quality and patient happiness in the setting of faith-based hospitals. This study seeks to fill this empirical void by investigating the correlation between service quality, patient satisfaction, and the intention to recommend a faith-based private hospital. An empirical study was carried out from October to November 2022, with a sample of 200 participants who underwent medical treatment at religiously affiliated facilities in Manado, North Sulawesi, Indonesia. The quantitative data were examined using structural equation modelling (SEM) using SmartPLS version 3.2. The results suggest that the quality of healthcare services has a favourable impact on consumer satisfaction. The intention to promote healthcare services is strongly influenced by patient satisfaction. Moreover, patient satisfaction completely mediates the association between healthcare service quality and recommendation intention. Furthermore, the study highlights reliability as the primary determinant in forecasting the quality of healthcare services. The findings enhance comprehension of the dynamics within faith-based hospital settings, guiding strategic initiatives to enhance healthcare delivery and patient outcomes.